Estimation of a total for rotated sample design using auxiliary information - Chadyšas , Viktoras (Lietuvos matematikos rinkinys, 2009)
In this paper we focus on constructions of the total estimator for rotated sampling design. Successive sampling procedure using multi-phase sampling design have been developed. The composite ratio type estimator of the total using auxiliary  information and its approximate variance is constructed under simple random sampling design on each phase.
Keywords: total estimator; sample rotation; multi-phase sampling; simple random sampling